Associated Of Nurses Motivation With Implementation Of Nurses Therapeutic Communications In Mitra Medika Hospital Medan - Yuniati, Yuniati; Wahyuni, Wahyuni; Harahap, Hasanah Pratiwi (School of Nursing, Faculty of Medicine, Tanjungpura University, 2020)
Background: Communication is a tool for nurses to influence patient behaviour in implementing nursing care. Communication can be done verbally or non-verbally. Verbal means words both orally and in writing, while non-verbal means without words. Objective: This study aimed to determine the relationship between Nurse Motivation and the Application of Therapeutic Communication for Nurses in the Inpatient Room of Mitra Medika Hospital, Medan, in 2020. Method: This study used an analytic survey research design with a cross-sectional approach, using the continuity correction test. The population in this study were nurses who worked at Mitra Medika Hospital Medan by totaled 74 respondents. The sample wer takem from all numbers of population by using total population. The type of data was primary data. The data analysis was univariate analysis and bivariate analysis. Results: there was a relationship between the motivation of nurses and the application of therapeutic communication by nurses in Mitra Medika Hospital Medan in 2020 with p-value = .003. Conclusion: relationship between the motivation of nurses and the application of therapeutic communication by nurses in Mitra Medika Hospital Medan in 2020.